PERTUMBUHAN DAN HASIL TIGA VARIETAS KEDELAI DI GAWANGAN DENGAN PEMOTONGAN UJUNG PELEPAH KELAPA SAWIT - Iqbal Effendy; Novianto Novianto; Dia Utami (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2020)
Oil palm plantations in Indonesia are the largest one in the world, reaching 12.3 million hectares, around 46% are smallholders with very low productivity couse income of oil palm farmers is very low. One effort to take over the problems is to develop an intercroping pattern of soybean- oilpalm by trimming the tips of the midribs of oil palm plants on thewider side of interspace of palm stand rows, to increase light interception accepted by soy bean plant surfaces. This study used a randomized block design (RBD) arranged in factorial 4x3 with three replications. The first treatment is cutting the edge of the oil palm midrib, namely P1 = 50 cm, P2 = 100 cm, P3 = 150 cm. The second treatment was low light intensity tolerant soybean varieties, namely: V1 = Dena 1, V2 = Anjasmoro and V3 = Detam 1. Other actions were carried out according to generally accepted standards. To see the effect of treatment carried out the F test at the level of 5%, and continued with the HSD test at the level of 5% to see the difference among treatments. The results showed that a hope of developing soybean plants as intercrops, although statistically did not show a significant difference. FFB results were not significantly affected by the act of trimming the midrib as 150 cm.